PENGARUH MODEL MAKE A MATCH TERHADAP PEROLEHAN BELAJAR PENDIDIKAN KEWARGANEGARAAN SDN 09 PONTIANAK BARAT - Lusiana Lusiana; Marzuki Marzuki; Sugiyono Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
Abstract This research aims to describe  the influence of the use of a model Make a Match of the results of the learning civic eduacation  a student of class V SDN 09 West Pontianak. Research method used is experimental method with Quasi Eksperimental Design with Design Nonequivalent Control Group Design. Population in this research is all students grade V B and V C academic year 2016 / 2017 which consisted of 68 people. Subjects of the sample were V B students consisting of 34 students (experiments) and 34 students (control) V C class. The research instrument is a matter of multiple choice test with 35 questions. Based on data analysis, the average of post test control class result is 60,06 and average result of post test of experiment class 70,24. Based on the T test obtained tarithmetic 3,6930 and ttable α = 5% equal to 1,998, which means tarithmetic (3,6930)> ttabel (1,998),  then alternative hypothesis be accepted.  Of reckoning as effect size (ES), obtained effect size  of 0,96 ( high criteria ) . This means that the use of Make a Match model gives a high influences on students civic education learning outcomes in class V SDN 09 West Pontianak.  Keyword : Influence, Make a Match Learning of Model, Learning Result, Civic Education